Integration Of Maqasid Shari'Ah In The Economic Cycle: Building The Connection Between Production, Distribution, And Consumption To Achieve Falah (Holistic Well-Being) - Peti Verawati; Kamaludin Kamaludin; Slamet Munawar (INSANI: Jurnal Ilmu Agama dan Pendidikan, 2026)
The increasing wealth inequality, structural poverty, and environmental degradation indicate the need for an economic paradigm that emphasizes not only growth but also justice and sustainability. Islamic economics offers an alternative framework through the concept of Maqāṣid Sharī'ah, which serves as the normative foundation for all economic activities. This study aims to analyze the integration of Maqāṣid Sharī'ah into the Islamic economic cycle, encompassing production, distribution, and consumption, in order to achieve Falāḥ (holistic well-being). This research employs a qualitative method with a library research approach. Data were collected from classical and contemporary literature on Maqāṣid Sharī'ah, Islamic economics, and relevant scholarly publications. Data analysis was conducted using content analysis to identify the relationship between the objectives of Islamic law and economic activities. The findings reveal that Maqāṣid Sharī'ah functions as an ethical framework that guides production toward maslahah and sustainability, distribution toward economic justice through ZISWAF instruments, and consumption toward balanced and responsible behavior. The integration of these three pillars plays a crucial role in ensuring the fulfillment of essential human needs (ḍarūriyyāt) and in achieving Falāḥ as the ultimate objective of Islamic economics. This study highlights that the comprehensive implementation of Maqāṣid Sharī'ah can contribute to the development of a more just, inclusive, and sustainable economic system.